2016
DOI: 10.1063/1.4966956
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin IBAD MgO films for epitaxial growth on amorphous substrates and sub-50 nm membranes

Abstract: A fabrication process has been developed for high energy ion beam assisted deposition (IBAD) biaxial texturing of ultrathin (∼1 nm) MgO films, using a high ion-to-atom ratio and post-deposition annealing instead of a homoepitaxial MgO layer. These films serve as the seed layer for epitaxial growth of materials on amorphous substrates such as electron/X-ray transparent membranes or nanocalorimetry devices. Stress measurements and atomic force microscopy of the MgO films reveal decreased stress and surface rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…4(f)]. At a high IAR of 0.79, the 5 nm thick IBAD-MgO film exhibited a strong in-plane texture of 6°, consistent with the previous work studied by Siming Wang et al 17) They fabricated an ultra-thin (∼1 nm) IBAD-MgO film using a very high IAR of 0.9. In terms of low IARs (0.2, 0.34, and 0.47), the biaxial texture was maintained in the IBAD-MgO layer when the thickness increased up to 50-60 nm, which was the highest value explored.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…4(f)]. At a high IAR of 0.79, the 5 nm thick IBAD-MgO film exhibited a strong in-plane texture of 6°, consistent with the previous work studied by Siming Wang et al 17) They fabricated an ultra-thin (∼1 nm) IBAD-MgO film using a very high IAR of 0.9. In terms of low IARs (0.2, 0.34, and 0.47), the biaxial texture was maintained in the IBAD-MgO layer when the thickness increased up to 50-60 nm, which was the highest value explored.…”
Section: Resultssupporting
confidence: 88%
“…Due to the strong binding force between the MgO atoms and the amorphous Y 2 O 3 layer, the MgO films exhibit a layer-by-layer growth mode at the initial stage. We speculate that it is the reason why ultra-thin (∼1 nm) IBAD-MgO films exhibiting excellent biaxial texture were obtained by S. Wang et al 17) When the Y 2 O 3 layer is completely covered by MgO atoms, the transition from the layer-by-layer to island-based growth of IBAD-MgO occurs, which would make the surface rougher. It is reported that the roughness of IBAD-MgO increases during film thickening.…”
Section: -4mentioning
confidence: 89%
See 1 more Smart Citation
“…First, Hastelloy shows an excellent corrosion resistance than pure metal foils under diverse electrolyte conditions such as acids, bases, and seawater atmosphere. Besides, Hastelloy C-276 shows high thermal resistance to form crystalline phases under a high-temperature process, indicating that Hastelloy is an appropriate candidate to fabricate films at high temperature. In addition, Hastelloy has an advantage in growing various crystalline thin films by using lattice matching by inserting well-known stable template layers such as Al 2 O 3 , Y 2 O 3 , and MgO. Accordingly, Hastelloy has been widely used for the growth of crystalline thin films in various fields, including superconductors, , ferroelectrics, optoelectronics, and solar cells; , that is, the crystalline photoelectrode can also be sufficiently fabricated on Hastelloy substrates through template engineering.…”
Section: Introductionmentioning
confidence: 99%